Control of T Cell Metabolism by Cytokines and Hormones - Bishop, Emma L.; Gudgeon, Nancy; Dimeloe, Sarah (Frontiers in Immunology, 2021)
Dynamic, coordinated changes in metabolic pathway activity underpin the protective and inflammatory activity of T cells, through provision of energy and biosynthetic precursors for effector functions, as well as direct effects of metabolic enzymes, intermediates and end-products on signalling pathways and transcriptional mechanisms. Consequently, it has become increasingly clear that the metabolic status of the tissue microenvironment directly influences T cell activity, with changes in nutrient and/or metabolite abundance leading to dysfunctional T cell metabolism and interlinked immune function. Emerging evidence now indicates that additional signals are integrated by T cells to determine their overall metabolic phenotype, including those arising from interaction with cytokines and hormones in their environment. The impact of these on T cell metabolism, the mechanisms involved and the pathological implications are discussed in this review article.